Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
7^x : 49 =7^27
=> 7^x = 7^27 . 7^2
=> 7^x = 7^29
=> x = 29
Vậy x = 29
\(7^x\cdot49=7^{27}\)
\(7^x\cdot7^2=7^{27}\)
\(7^x=7^{27}:7^2\)
\(7^x=7^{25}\)
\(x=25\)
Ta có -49/63=-21/27
Mà y/27=-21/27 suy ra y=-21
Lại có -21/27=-7/9
Mà 7/x=-7/9 suy ra x=-9
Vậy x=-9;y=-21
\(\frac{7}{x}=\frac{y}{27}=\frac{-49}{63}\)
Ta có:
\(\frac{7}{x}=\frac{-49}{63}\)
\(\Rightarrow-49.x=7.63\)
\(\Rightarrow-49x=441\)
\(\Rightarrow x=441:\left(-49\right)\)
\(\Rightarrow x=-9\)
\(\frac{y}{27}=\frac{-49}{63}\)
\(\Rightarrow y.63=-49.27\)
\(\Rightarrow63y=-1323\)
\(\Rightarrow y=\left(-1323\right):63\)
\(\Rightarrow y=-21\)
Vậy x = -9 ; y = -21
7x . 49 = 727
7x . 72 = 727
7x = 727 : 72
7x = 725
x = 25
Vậy x = 25
a) 3x - 21 = 27
3x = 27 + 21
3x= 48
x = 48 : 3
x= 16
b) -7 - x + 14 = 49
-7 - x = 49 - 14
-7 - x = 35
x = 35 : (-7)
x = -5
75x : 49 = 728
=> 75x : 72 = 728
=> 75x - 2 = 28
=> 5x - 2 = 28
=> 5x = 30
=> x = 30 : 5
=> x = 6
b) 2x - 5 = 27
=> 2x = 27 + 5
=> 2x = 32
=> 2x = 25
=> x = 5
c) (x4)5 = x
=> x4.5 = x
=> x20 = x
=> x20 - x = 0
=> x(x19 - 1) = 0
=> \(\orbr{\begin{cases}x=0\\x^{19}-1=0\end{cases}}\)=> \(\orbr{\begin{cases}x=0\\x^{19}=1\end{cases}}\)=> \(\orbr{\begin{cases}x=0\\x^{19}=1^{19}\end{cases}}\)=> \(\orbr{\begin{cases}x=0\\x=\pm1\end{cases}}\)
Vậy \(x\in\left\{-1;0;1\right\}\)
\(a,7^{5x}:49=7^{28}\)
\(7^{5x}:7^2=7^{28}\)
\(7^{5x-2}=7^{28}\)
\(\Rightarrow5x-2=28\)\(\Rightarrow5x=30\)\(\Rightarrow x=6\)
\(b,2^x-5=27\)\(\Rightarrow2^x=32\)\(\Rightarrow2^x=2^5\Rightarrow x=5\)
\(c,\left(x^4\right)^5=x\)
\(\Rightarrow x^{20}=x\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
\(7^x:49=7^{27}\)
\(7^x:7^2=7^{27}\)
\(7^x\) \(=7^{27}.7^2=7^{29}\)
Vậy x = 29
K mk mk đầu tiên nhá
\(7^x:49=7^{27}\)
\(\Rightarrow7^x:49=49^{26}\)
\(\Rightarrow7^x=49^{26}:49=49^{25}\)
\(\Rightarrow x=25\)
tíc mình nha